Composition of the chilean Constitutional Tribunal: A critic perspective to the appointment and nomination system - Salem Gesell, Catalina (Derecho Público Iberoamericano, 2017)
The present article analyses the power of nomination and appointment system of the Chilean constitutional judges. The analysis concludes that the actual system does not achieve a standard of suitable checks and balances. Thus, a new system of designation is proposed as an alternative to the autonomous repartition of nominations made by the President of the Republic, the National Congress and the Supreme Court, in which the same institutions participate, but through a counterbalanced concurrence of wills. This also reinforces the legitimacy of the Constitutional Tribunal.